Alterations of drug disposition in high altitude - Ritschel, Wolfgang A. (1998)
Exposure of the human body to high altitude (H) results in significant physiologic changes and may precipitate mountain sickness, ranging from mild symptoms above 2500 m to severe symptoms above 4000 m, and coma a teven higher altitude. In a previous study in our labs we found et vivo an increase in meperidine (M) upteke wilh increase in number of erythrocytes (RBG). One of the major physiologic changes at H is a increase in hematocrit and RBC. The study was carried out in three groups of healthy volunteers (18-2' y): at sea level (L), at 4360 m the day after arrival at H (HA), and at 4360 m in subjects residing > 10 mo at H (HC), 0.75 mglkg of M was administered I.M. between 8-9 a.m. Blood was collected for 12 h. M was measured in whole blood (WB), plasma (P) and plasma -water (PW). The pharmacokinetic parameters derived from curve-fitting were analyzed by ANOVA. Significant changes were found in P and (WB) for λz ↓ L vs HA (L vs HA), L vs HC; CL/F ↓ L vs HA (L vs HA), L vs HC, and MRT ↑ L vs HA (L vs HA), L vs HC. The hematocrit significantly increased L vs HA, L vs HC end HA vs HC from 43.3 to 46.4 to 53.4%. The RBC binding significantly increase from 42.3% at L to 43.8% at HA to 50.9% at GC. The extent 01 protein binding shows a trend to decrease with H, however, it is not significant. Free M concentration in PW measured after 1,2, and 4 h was significently increased after 2 and 4 h.